Protecting Local Cultural Heritage In South Sumatera: Agenda-Setting Policy - Husyam, Husyam; Sobri, Kiagus Muhammad; Alfatih, Andy; Alamsyah, Alamsyah (UNIVERSITAS PAKUAN, 2017)
Identity and local cultural heritage are different aspects, but having played important elements which create character, identity which must be preserve and maintain properly. The paper aims to analyze and examine the public policy formulation of Regional Regulation (Peraturan Daerah) number 2 of 2021 concerning the ornament building with special identity of South Sumatera. The study is undertaken through qualitative methods, through modelling case study in Palembang, applying with the Multiple Streams Framework (MSF) to highlight how several elements or streams interact to affect the acceptance of particular policies. This paper reveals that, the Regional Regulation has successfully ratified though the important role of Governor as policy entrepreneurial. Therefore, by applying MSF theory has utilizes public policy process in the preservation cultural heritage in South Sumatera context. It also recommends further policy through the establishment of cultural heritage conservation agencies, which can collaborate with local communities, researchers, and experts to develop effective preservation strategies.